(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Autism Spectrum Disorder (ASD) affects approximately 1 in 36 children in the United States, presenting unique challenges that require multifaceted support systems. This paper explores the thematic elements of collaborative approaches in supporting children with ASD, examining the critical roles of interdisciplinary teams, family-cantered interventions, school-based partnerships, and community resources. Through a comprehensive review of current literature and evidence-based practices, this study identifies key collaborative frameworks that enhance outcomes for children with ASD. The findings emphasize that successful support for children with ASD requires coordinated efforts among healthcare professionals, educators, families, and community members. This collaborative approach not only addresses the core symptoms of ASD but also promotes social integration, academic achievement, and overall quality of life for affected children and their families.